The Role of Augmented Reality in English Language Learning: Increasing Engagement and Cultural Immersion - Danial, Haris; Karimah, Saidatul; Mafruhah, Anisatul; Karomi Safari, M. Ubaidillah; Chai, Nong (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Augmented reality (AR) is increasingly being integrated into education, enhancing learning experiences through interactive and immersive environments. In language learning, AR holds promise for increasing engagement and cultural immersion. Purpose. To investigate the impact of AR on English language learning, comparing engagement and cultural immersion in formal and informal contexts. Method. Mixed-methods approach involving middle school, high school, and university students. Participants were divided into experimental (AR) and control (traditional methods) groups. Data were collected through pre- and post-tests, surveys, and interviews to measure language proficiency, engagement, and cultural awareness. Results. Significant improvements were observed in both learning contexts. In formal settings, there was a 17% increase in test scores, while informal settings saw a 13% increase. Formal learners exhibited higher engagement and cultural awareness, with 80% reporting high engagement compared to 70% in informal settings. Formal learners frequently utilized interactive features, enhancing their learning experience, whereas informal learners showed a preference for independent study tools offered by AR applications. Conclusion. AR significantly enhances English language learning, particularly within formal educational environments. The study highlights AR's potential to boost student engagement and cultural understanding, suggesting that tailored approaches are necessary to optimize its use across different learning contexts. The findings indicate that while both formal and informal settings benefit from AR, the structured environment of formal education leverages the technology's interactive features more effectively, leading to greater student engagement and improved learning outcomes. These insights are valuable for educators and developers aiming to integrate AR in language learning, emphasizing the need for context-specific strategies to maximize its educational benefits.